Preclinical assessment of CAR-NK cell-mediated killing efficacy and pharmacokinetics in a rapid zebrafish xenograft model of metastatic breast cancer - Nivedha Murali Shankar; Nivedha Murali Shankar; Nivedha Murali Shankar; Nivedha Murali Shankar; Paola Ortiz-Montero; Paola Ortiz-Montero; Anastasia Kurzyukova; Anastasia Kurzyukova; Wiebke Rackwitz; Wiebke Rackwitz; Stephan R. Künzel; Stephan R. Künzel; et al. (Frontiers in Immunology, 2023)
Natural killer (NK) cells are attractive effectors for adoptive immunotherapy of cancer. Results from first-in-human studies using chimeric antigen receptor (CAR)-engineered primary NK cells and NK-92 cells are encouraging in terms of efficacy and safety. In order to further improve treatment strategies and to test the efficacy of CAR-NK cells in a personalized manner, preclinical screening assays using patient-derived tumor samples are needed. Zebrafish (Danio rerio) embryos and larvae represent an attractive xenograft model to study growth and dissemination of patient-derived tumor cells because of their superb live cell imaging properties. Injection into the organism’s circulation allows investigation of metastasis, cancer cell-to-immune cell-interactions and studies of the tumor cell response to anti-cancer drugs. Here, we established a zebrafish larval xenograft model to test the efficacy of CAR-NK cells against metastatic breast cancer in vivo by injecting metastatic breast cancer cells followed by CAR-NK cell injection into the Duct of Cuvier (DoC). We validated the functionality of the system with two different CAR-NK cell lines specific for PD-L1 and ErbB2 (PD-L1.CAR NK-92 and ErbB2.CAR NK-92 cells) against the PD-L1-expressing MDA-MB-231 and ErbB2-expressing MDA-MB-453 breast cancer cell lines. Injected cancer cells were viable and populated peripheral regions of the larvae, including the caudal hematopoietic tissue (CHT), simulating homing of cancer cells to blood forming sites. CAR-NK cells injected 2.5 hours later migrated to the CHT and rapidly eliminated individual cancer cells throughout the organism. Unmodified NK-92 also demonstrated minor in vivo cytotoxicity. Confocal live-cell imaging demonstrated intravascular migration and real-time interaction of CAR-NK cells with MDA-MB-231 cells, explaining the rapid and effective in vivo cytotoxicity. Thus, our data suggest that zebrafish larvae can be used for rapid and cost-effective in vivo assessment of CAR-NK cell potency and to predict patient response to therapy.